Faktor - Faktor yang Berpengaruh Terhadap Return On Asset Perusahaan yang Terdaftar di BEI Sub Sektor Perdagangan Besar Barang Produksi Tahun 2010 – 2014 - Rullianty, Debby Ayummy (EKONOMIA, 2019)
This study aims to analyze the influence of Current Ratio (CR), Total Assets Turnover (TATO), Debt Ratio to Equity Ratio (DER), and Sales to Return On Assets (ROA) of companies listed in the BEI sub-sector of goods trade in 2010 - 2014.The tools of analysis used in this study is Linear Regression Analysis that can be used to predict the significance of the function or causality between a dependent variable (Y) Based on the calculation results show that the Current Ratio (CR) is significant to RetunOn Assets (ROA) on the goods trading sub-sector listed on the BEI 2010 - 2014. Total Asset Turnover (TATO) significant to Retun On Assets (ROA) sub-sector of trade of goods manufactured in BEI 2010 - 2014. Debt to Equity Ratio (DER) is not significant to Retun On Assets (ROA) in goods trading sub-sector listed on BEI 2010 - 2014. Sales not significant to Retun On Assets (ROA) on the goods trading sub-sector listed on the Stock Exchange 2010 - 2014.